Febrile pleuropericarditis, a potentially life-threatening adverse event of balsalazide – case report and literature review of the side effects of 5-aminosalicylates. (May 2014) - Coman, Roxana M; Glover, Sarah C; Gjymishka, Altin
<x xml:space="preserve">Abstract</x> Ulcerative colitis (UC) is an idiopathic chronic inflammatory disorder that affects the colonic mucosa. One class among the drugs used for its treatment is the 5-aminosalicylates (5-ASAs). While highly efficacious in treating mild-to-moderate UC, 5-ASAs are associated with rare but potentially life-threatening side effects such as pericarditis, myocarditis and pneumonitis. These adverse events appear to be caused by a hypersensitivity reaction and resolve after cessation of 5-ASA drugs. This article presents a case report of febrile pleuropericarditis in a UC patient treated with balsalazide, and provides a thorough literature review of the rare side effects of 5-ASAs, their incidence, clinical presentation, differential diagnosis and treatment. In conclusion, the clinicians should be aware that this type of adverse events to 5-ASA compounds can be easily overlooked but it has significant morbidity if not promptly diagnosed.